CONTINUOUS OBSTETRIC CARE (CONTINUITY OF CARE) IN NEWBORNS WITH MILD ASPHYXIA AT PRATAMA NIAR CLINIC MEDAN INDONESIA 2025 - Pasaribu, Novalita Eudia; Ribur Sinaga; Febriana Sari; Efra Tasiya Sitio; Apriyanis Waruwu; Nitaria Sonata Sinaga; Sri Yanti Kristin (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Neonatal asphyxia remains one of the leading causes of neonatal morbidity and mortality, particularly in developing countries. Timely and continuous obstetric care is essential to prevent complications and improve neonatal outcomes.(Kemenkes, 2023) Objective: This study aimed to describe the implementation of continuous obstetric care in a newborn with mild asphyxia at Pratama Niar Clinic, Medan. Methods: This study used a descriptive case study design conducted from November 2024 to February 2025. Data were collected through observation, interviews, physical examinations, and review of maternal and child health records. Care was provided continuously from antenatal, intrapartum, to postnatal periods. Results: The newborn experienced mild asphyxia associated with meconium-stained amniotic fluid and maternal factors.(Lee et al., 2025) .Immediate neonatal resuscitation followed by post-resuscitation care resulted in stable neonatal condition with a normal APGAR score. Continuous monitoring and early initiation of breastfeeding supported neonatal recovery. Conclusion: Continuous obstetric care enables early detection, prompt management, and effective prevention of complications in newborns with mild asphyxia. This approach contributes to improved neonatal outcomes and maternal understanding of pregnancy and childbirth risks.(Julyanti and Susilawati, 2024)